TEKNIK PENJEBAKAN (ENTRAPMENT) DALAM PENYIDIKAN DI INDONESIA - Febrina, Cokorda Istri Bella; Maharani, I Gusti Ayu Stefani Ratna (Kertha Desa; Vol 10 No 7 (2022), 2022)
The purpose of this research is to find out the qualifications of entrapment techniques in the process of investigation and investigation to avoid the arbitrariness of investigators and to determine future arrangements regarding entrapment techniques in the Criminal Procedure Code. The method used in this study is the normative legal research method. The entrapment technique in uncovering a criminal offense cannot be solely carried out in ordinary criminal cases. This entrapment technique can only be carried out by investigators in uncovering narcotics crime because narcotics crime is an organized crime and extraordinary crime, besides that in Law Number 35 Year 2009 concerning Narcotics also has set about covert buying techniques which contain entrapment technique. The unregulated regulation regarding entrapment techniques in the Criminal Procedure Code raises the void of norms which results in the legitimacy of entrapping techniques in revealing an ordinary crime.